Analytical Thermodynamics - Li, Dongqing; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides the foundations of analytical thermodynamics for graduate level. The content is based on the author$1 (Bs lecture notes developed over 30 years of academic teaching. It aims to present thermodynamics to the readers as easy to understand as possible, being suitable for professors teaching advanced thermodynamics or graduate students learning thermodynamics. The chapters include the basics of analytical thermodynamics, modelling of homogeneous and heterogeneous systems, thermodynamics of interfaces and three-phase contact lines and the Second Law in engineering thermodynamics.s
Analytical Thermodynamics: Chapter 1.Basics of Analytical Thermodynamics.-Chapter 2 Modelling Homogeneous and Heterogeneous Systems -- Chapter 3. Thermodynamics of interfaces and three-phase contact lines -- Chapter 4.Second Law in Engineering Thermodynamics.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Thermodynamics, Heat and Mass Transfer; Thermodynamics